2013
DOI: 10.1155/2013/634832
|View full text |Cite
|
Sign up to set email alerts
|

HyDEn: A Hybrid Steganocryptographic Approach for Data Encryption Using Randomized Error-Correcting DNA Codes

Abstract: This paper presents a novel hybrid DNA encryption (HyDEn) approach that uses randomized assignments of unique error-correcting DNA Hamming code words for single characters in the extended ASCII set. HyDEn relies on custom-built quaternary codes and a private key used in the randomized assignment of code words and the cyclic permutations applied on the encoded message. Along with its ability to detect and correct errors, HyDEn equals or outperforms existing cryptographic methods and represents a promising in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…Recently, it has been shown that the genome of a genetically tractable organism can be used as a medium for data hiding depending on the required application [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The coding DNA of a gene is transcribed by codons of three nucleotide bases that specify amino acids to encode proteins.…”
Section: Requirements Of Reversible Data Hiding In Dna Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that the genome of a genetically tractable organism can be used as a medium for data hiding depending on the required application [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The coding DNA of a gene is transcribed by codons of three nucleotide bases that specify amino acids to encode proteins.…”
Section: Requirements Of Reversible Data Hiding In Dna Sequencementioning
confidence: 99%
“…Rapid progress in synthesizing defined strings of DNA and sequencing the data saved in DNA has enhanced the feasibility of DNA storage. In addition to DNA storage [1][2][3], DNA steganography for secret communication or encryption using noncoding DNA sequences [4][5][6] has been widely studied for decades. Recent years have witnessed the use of coding DNA sequences to investigate DNA watermarking for tracking parent genes in offspring or genetically modified organisms and for protecting DNA copyright [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of the selected s are used. In recent years, many steganography were proposed with considering the cracking probability [44][45][46][47][48][49][50][51] under a brute force guessing. The threating mode evaluated here is based on the intruders knowing algorithms but without the order R. In practice, R is a private key and it should be transmitted via a secure channel.…”
Section: Performances Under Other Attacksmentioning
confidence: 99%
“…, 비밀 통신위한 DNA 스테가 노그라픽 [2], 및 GMO(genetically modified organism) 또는 서열의 인증 및 저작권 보호위한 DNA 워 터마킹 기술 [3]- [5] …”
unclassified